2010
DOI: 10.1179/dfi.2010.003
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Drivability of Open Ended Piles in Very Dense Sands

Abstract: The successful installation of long piles driven into very dense sands relies on the occurrence of the reduction in local friction with increased pile embedment, a phenomenon known as 'friction fatigue'. The underlying mechanisms controlling friction fatigue are poorly understood, with some design methods including an adjustment for the influence of pile diameter while others do not. This paper back calculates the installation resistance of 0.356m to 2m (14in to 78in) diameter open ended piles driven into very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
1
18
0
6
Order By: Relevance
“…Predictions based on the IC-05 (Jardine et al, 2005) methodology 102 which accounts for high strength of the clay, the pile geometry, group effects and cyclic loading 103 provided much more consistent estimates of the pile resistance than standard offshore methods. 104 Schneider and Harmon (2010) proposed a pile driveability model based on the UWA-05 (Lehane et al,105 2005) method that incorporates friction fatigue and accounts for the effects of pile plugging. They note 106 that inertial effects during driving mean that the soil plug remains at or near the sea bed level during 107…”
Section: Introduction 71mentioning
confidence: 99%
“…Predictions based on the IC-05 (Jardine et al, 2005) methodology 102 which accounts for high strength of the clay, the pile geometry, group effects and cyclic loading 103 provided much more consistent estimates of the pile resistance than standard offshore methods. 104 Schneider and Harmon (2010) proposed a pile driveability model based on the UWA-05 (Lehane et al,105 2005) method that incorporates friction fatigue and accounts for the effects of pile plugging. They note 106 that inertial effects during driving mean that the soil plug remains at or near the sea bed level during 107…”
Section: Introduction 71mentioning
confidence: 99%
“…Because the term causes the shape of the shear resistance distribution to change with pile penetration, some averaging technique is necessary. Schneider and Harmon (2010) found that the shape of the shaft friction distribution had a negligible effect on the resultant bearing graph. They suggest the change in shaft capacity between two successive depth increments be used to calculate the pseudo average shaft 2.…”
Section: Modelling Processmentioning
confidence: 97%
“…Predictions based on the IC-05 (Jardine et al, 2005) methodology which accounts for high strength of the clay, the pile geometry, group effects and cyclic loading provided much more consistent estimates of the pile resistance than standard offshore methods. Schneider and Harmon (2010) proposed a pile driveability model based on the UWA-05 (Lehane et al, 2005) method that incorporates friction fatigue and accounts for the effects of pile plugging. They note that inertial effects during driving mean that the soil plug remains at or near the sea bed level during installation.…”
Section: Introductionmentioning
confidence: 99%
“…Häufig genutzt werden z. B. die Methoden nach Stevens et al sowie Alm und Hamre mit Mittelung nach Schneider und Harmon . Insbesondere in veränderlichen festen Gesteinen, z.…”
Section: Einleitung Und Motivationunclassified
“… Verfahren nach Alm und Hamre mit Mittelung nach Schneider und Harmon , Verfahren nach Schmertmann mit Bodenklassifikation nach Robertson et al , Verfahren nach Stevens et al mit Bezug auf das API . …”
Section: Static Resistance To Driving (Srd)unclassified